Always a catch! : how I punched my way into marrying a prince, 2 - Momoyo, Mayo; Mito, Itsuki (Always a Catch!, 2025)
"The road to the alar may have some bumps along the way! Eligible young bachelorette Maria Annovazzi of Muro has managed to sort out a case of mistaken identity and win herself an admirer of her fighting skills. Now she's happily engaged to said admirer, Prince Renato of Rubini. While her future should be set, troubles await her back at home... Maria arrives for a visit with her family, only to find that her father - who's also her martial arts master - is acting strange. Does a family spar stand between Maria and her happy ending?" --